Internet of things. IoT infrastructures : second International Summit, IoT 360° 2015, Rome, Italy, October 27-29, 2015. Revised selected papers /: IoT infrastructures : second International Summit, IoT 360° 2015, Rome, Italy, October 27-29, 2015. Revised selected papers. Part II : (2016) - Unknown
No abstract available